Kajian Pustaka Karakterisasi Perekat Polivinil Asetat Berbasis Air dengan Variabel Surfaktan: Water Base Polyvinyl Acetate Characterization with Surfactant Variable – a Review - Rony Pasonang Sihombing; Dieni Nurul Fathiyyah; Nanda Liant Kumara; Agustinus Ngatin (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
Polyvinyl acetate (PVAc) is an applicative polymer used as an adhesive material for one to another. These polymers can be synthesized through an emulsion polymerization process. In the industrial world, the process of making adhesive still involves environmentally unfriendly organic compounds containing xylene, benzene, and toluene. Therefore, water-based adhesive was introduced as an alternative to the PVAc synthesis solution. The aim of this literature review is to identify the type of surfactants used and analyze the PVAc characterization. This literature study focuses on the characterization of water-based PVAc with non-ionic nonylphenol (NP) surfactants including: NP-06, NP-10, NP 10 + 30, NP-30 and NP-40. Another surfactant used in this literature study is anionic surfactant Sodium Lauryl Sulfate (SLS) in units of Critical Micelle Concentration (CMC) including 1 CMC, 3 CMC, 5 CMC, 10 CMC, and 15 CMC. The result is a similarity in phenomena between the two types of surfactants. There is an increase in viscosity and a decrease in the value of the particle size as the surfactant increasing concentration used. However, in terms of the particle size, there is an optimal value where the specific NP surfactant concentration produces specific particle size with grit and at the specific SLS surfactant concentration produces relatively similar particle size.